The Arc of Migration and the Impact on Children's Health and Well-Being: Forward to the Special Issue-Children on the Move - Charles Oberg (MDPI AG, 2019)
Since the start of this millennium the diaspora of families with children has continued unabated. UNICEF estimates that nearly 31 million children have been forcibly displaced from their homes by the end of 2017. This includes 13 million child refugees, an estimated 17 million children internally displaced within their own countries and over 900 thousand children seeking asylum in a different country. Even more staggering is the 75 percent increase in the number of child refugees between 2010 and 2015. This Special Issue, Children on the Move: The Health of Refugee, Immigrant and Displaced Children, examines in detail the health and well-being of our most vulnerable children today. It follows the arc of migration from home country, through transit and finally the challenges experienced in a child’s new country. The papers explore a variety of acute and chronic health conditions as well as the mental health of these children and youth. The articles examine the trauma experienced in their home country, the fleeing of war, violence and/or poverty, the travails during their journey, the stress throughout their stay in detention centers and refugee camps, and finally the transition to a new home country.